ROLE OF INTERNATIONAL MARKETING IN GLOBAL ENTREPRENEURSHIP (Economic journal of Lesya Ukrainka Volyn National University, 2020)
The statistic has a glance at the interpretation of the term "international marketing"; view of international marketing; it is shown that the passages and shortcomings of international marketing are described. Vіtchiznyans and foreign sciences are responsible for the role of marketing functions in the management of all kinds of people in the global market. So, the results show that the marketing function in the development of financial indicators, the efficiency of new products with customers, and the profitability of new products on the market.     The order of sorts of naukovtsi talk about those that are less important for marketing as functions, and more for the meaning of the rules, so that marketing is transformed into an independent process.     Naked on the importance of global international management; presents the process of international marketing strategic plan. Internal drivers - ti, which resemble a company and, in such a rank, are controlled by a server, such as a global capacity and functionality of a company, as well as financing and international availability of kervniks.      On the other hand, the name of the drivers is not controlled by the brand, but it does not add a global strategy to the state of affairs. Among these factors is the global economy, culture, political and legal systems and technologies. The system of global marketing has been discussed, and I have a lot of respect for the fallow land: Global Marketing Performance.It is said about the importance in the global education of the national culture of the country, on the plan to start the enterprise out of its products; Proposed come back to the global community for help with international marketing
Keywords: international marketing, global enterprise, marketing strategic planning, marketing technologies, international marketing medium